Blood on the water - Perry, Anne (New York : Ballantine Books, 2014)
"Though Monk is witness to the terrible bombing of an afternoon pleasure boat on the river that leaves 200 people dead, much to his dismay the case is taken from his hands and given over to the commissioner of police. An Egyptian man is quickly caught, tried, and sentenced to death--and then just as swiftly murdered in prison. When evidence surfaces that proves the dead man innocent, the case is handed back to Monk, who must now rely on his own memory of the event to help piece together what really happened. His investigation leads him down a dangerous road, one in which wealthy and powerful men gamble for control of the Suez Canal, so crucial to the Empire's future. With his wife Hester and friend Oliver Rathbone, Monk soon reveals that the attack is not quite what it seems--but as he begins to unravel the motives behind it, he finds himself treading the dangerous waters of international political intrigue, where justice always comes with a price...and inadvertently makes himself the next target"--
BookPage
Publishers Weekly
Library Journal Prepub Alert
Keywords: Monk, William (Fictitious character) -- Fiction; Private investigators -- England -- London -- Fiction; London (England) -- Social conditions -- 19th century -- Fiction; Mystery fiction